The Integration of the Digital Platform Educaplay in Interdisciplinary Paths in the 1st and 2nd Basic Education Cycles - Vânia Graça; Paula Quadro-Flores; Altina Ramos (Athens Institute for Education and Research, 2022)
The dialogue between knowledge, pedagogies and didactic resources gives meaning to learning. This learning when integrated in a transdisciplinary environment enhances the holistic development of the child. This study is part of the Master's Degree in Education of the 1st Cycle of Basic Education and Portuguese and History and Geography of Portugal in the 2nd Cycle of Basic Education, integrated in the IFITIC Project "Innovate with ICT in Initial Teacher Training to Promote Methodological Renewal in Pre-school Education and in the 1st Cycle of Basic Education". The purpose of this research is to verify the potential of the digital educational platform Educaplay in the 1st and 2nd Basic Education Cycles. In this sense, the qualitative methodology was used, of an interpretative and comprehensive nature, since the aim is to analyze the social, valuing the meaning of action and the role of the subjects in the social construction of reality. The data were collected by the participating observation practice and field notes, since they allow access to facts, situations and behaviors, difficult to be captured through the survey or interview. In the first stage the educational practice was understood through the integration of digital resources and in the second stage the facts and their impacts were analyzed and interpreted. The sample involved 73 children, 21 children attending 3rd grade and 52 children from two classes attending 6th grade at a school in the Porto region. The results show that this platform has promoted: a) the appropriation of contents in a transversal and interdisciplinary way and b) the development of skills, values and attitudes inherent to the profile of the XXI century student. Thus, the article presents the educational practices that have integrated tools of Educaplay by the voice of the narrator. It is hoped that this research can provide pointers for teachers and educators seeking to renew their educational practices of vertical and horizontal articulation.